The Relationship between Activity Level of Some Lower Extremity Muscle and Anterior Shear Force during Single-Leg Jump Landing - Majid Fatahi; Farajollah Fatahi (Vesnu Publications, 2013)
Abstract   Introduction: Identifying factors which cause the high incidence of ACL is of great importance .Theanterior shear forces are the primary mechanism of load sustained on the ACL. During exercise, the activity of muscles and position of lower limbs may increase or decrease the anterior shear force. The purpose of this study is toinvestigate the relationship between the activity level of some lower extremity muscles and anterior shear force duringsingle-leg jump landing. Materials and Methods: Twenty male-students of physical education participated in this study. EMG activity of the musclesof thegluteus medius, tibialis anterior and hamstring were evaluated via Electromyography system andground reaction force was evaluated via force plate system in jump-landing task. There was used Pearson correlation test. Results: The results indicated no significant correlation between tibialis anterior and gluteus mediusmuscles activity with shear force, while there was found correlation between lateral hamstring muscleactivity and anterior shear force (P< 0.05). Conclusion: The findings of this study showed that hamstring muscle activity during single-leg jump landing acts as a supporting muscle of ACL. This increased muscle activity leads to the reduction of theload on the ACL. Keywords:Electromyography, Anterior Shear Force, Anterior Cruciate ligament, Jump-Landing task, Lower Extremity Muscles